Massive Water Production from Cryogenic Icy Lunar Regolith by a Microwave Heating Method - Qinggong Wang; Yong Pang; Juping Gu; Zhongxian Zhao; Qichen Sun; Mengfei Yang (Research)
Water extraction from lunar regolith is one of the critical techniques for in situ resource utilization on the Moon. Traditional conductive heating methods show low efficiencies for massive water production from lunar regolith due to the low heat conductivity of lunar regolith and the inherent harsh lunar environment. To enhance the effectiveness of massive water production and reduce energy cost, microwave heating method is used in this study to extract water from icy lunar regolith at an initial cryogenic temperature of −80 °C. Hydrated lunar regolith simulant (LRS) is prepared with the water content from 1.96% to 13.79%. The particles are compacted into large cylinder sample with a size of 70 mm (diameter) × 70 mm (height). An integrated microwave heating system is built by which the icy lunar regolith is heated by microwaves at 2.45 GHz. Water vapor is transmitted in a closed flow path, and liquid water is collected in a cold trap after condensation. Both a high-power heating pattern (800 W) and a low-power heating pattern (400 W) are studied. The results show that microwave heats the sample uniformly, and water content escapes from center to outside. At the high power of 800 W, the samples are dried almost completely at an energy cost of 1.9 to 10.0 W·h/g with the decrease of water content. The rate of water collection is up to 1.57 g/min. Reducing heating power to 400 W prolongs the initial heat input period. Once the liquid water begins to collect, the water collection rate is comparable to that at the high-power heating pattern. The results prove the effectiveness of microwave heating for massive water production from icy lunar regolith, and the technique can be used for future engineering applications.